Switching to quetiapine for risperidone-induced amenorrhea: Report of two cases - Pardal, P. K. (Medknow Publications & Media Pvt Ltd, 2010)
Almost all the antipsychotics can cause hyperprolactinemia-related side-effects like amenorrhea. Quetiapine has been reported to have minimal propensity to cause hyperprolactinemia. We report here two cases of risperidone-induced amenorrhea, who resumed their normal cycle on switching over the medication to quetiapine.